Effects of various fertilizer combinations on Okra (Abelmoschus esculentus L.) varieties for dietary fiber content and vegetative characteristic - Regmi, Bijay; Bhattarai, Kapil; Bhusal, Nama Raj; Poudel, Samip Raj; Kunwar, Samir (Himalayan Journal of Science and Technology, 2022)
A Field experiment using two determinate hybrid varieties of okra (Venus and Nitya) was conducted at Agriculture and Forestry University, Rampur, Chitwan during summer of 2021 to examine the impact of different fertilizer combinations on the dietary fiber content and vegetative characteristics of okra. This study was laid out in a split-plot design and comprised three replications; there were two main plots of Okra varieties, and each main plot contained four sub-plots of fertilizer combinations (Inorganic fertilizer + Poultry manure, Inorganic fertilizer + Vermicompost, Inorganic fertilizer + FYM, and Inorganic fertilizer alone). The experimental results revealed that the Venus variety had a higher dietary fiber content (3.52%) than the Nitya variety (2.98%). Venus variety (6.6 t/ha) had a higher yield as compared to the Nitya variety (5.3t/ha). It was observed that Inorganic fertilizer + Poultry manure (3.80%) followed by Inorganic fertilizer + Vermicompost (3.46 %) had a superior effect on the dietary fiber content of fruit. Inorganic fertilizer + Poultry manure produced the highest plant height (1.13 m), average canopy diameter (1.10 m), and yield (6.8 t/ha), while Inorganic fertilizer + FYM produced the highest pod length (11.81 cm). The results suggest that combined application of a recommended dose of inorganic fertilizer with organic fertilizer (Poultry manure) improves dietary fiber content and vegetative characteristics of the Okra plant .